Management of a Pregnancy Complicated by Pompe Disease - Jennifer Weida; B. E. Hainline; C. Bodkin; M. K. Williams (Hindawi Limited, 2012)
Background. As more women with metabolic muscle diseases reach reproductive age, knowledge of these diseases and their impact on pregnancy is necessary. Case. 23-year-old G1P0 with juvenile-onset Pompe disease (PD) delivered a viable infant by cesarean section at 32 weeks and 6 days. The pregnancy was complicated by worsening maternal pulmonary status, muscular strength, and mobility. Conclusion. The management of pregnancies complicated by Pompe disease requires a multidisciplinary approach, including expertise in neuromuscular disease, maternal-fetal medicine, biochemical genetics, pulmonology, anesthesia, and dietetics.